ChatGPT as a Cognitive Tool: A Study on Transformations in Indian Higher Educational Pedagogies - Rahul Dass, Anvesha Sharma, Monika Saxena, (European Economic Letters (EEL), 2024)
Artificial Intelligence based ChatGPT has taken the higher education ecosystem by a storm, forcing are-think on the current teaching pedagogy. A state of uncertainty has gripped the teaching community as efforts are on to mitigate the impact of ChatGPT on education at universities. This research paper does a deep dive into how ChatGPT is likely to irrevocably change how students learn and teachers teach. In a two-week class-room based experiment in our discussion-based News Analysis classes as well as lecture-based Marketing classes, we divided students into two equal groups. One group was allowed to use ChatGPT, while the other one was a control group. The ChatGPT group granted access once to use ChatGPT to find answers to tricky terms/queries, while the control group had no such AI-tool access. After the two-week period got over, it was found that the ChatGPT students had a steeper learning curve as compared to the control group. This research paper argues that ChatGPT can be effectively put to use in classroom-based teaching. It is a human-computer hybrid model in which this AI tool assists in regular teaching.